Factors associated with Knowledge of Healthy Community, Empowers Nation (KOSPEN) and its implementation among community health volunteers in Kulim district, 2017 - Sondaram, Navindra Kumar; Kadir @ Shahar, Hayati; Abdul Manaf, Rosliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: The increasing burden of Non-Communicable Diseases and their prevalence has led Ministry of Health (MOH) Malaysia to introduce a community empowerment program “Komuniti Sihat, Perkasa Negara” acronymed as KOSPEN in July 2013. Thirty thousand community health volunteers have been trained nationwide up to May 2015. Objective: To identify the factors associated with knowledge on KOSPEN and its implementation among community health volunteers in Kulim District. Methods: A cross-sectional study based on simple random sampling was conducted among community health volunteers Kulim District. Volunteers participated in this study were 194. Data collected using self-administered questionnaire. All data collected were analysed using IBM SPSS version 22 involving descriptive and inferential statistics with significance level set at 0.05. Results: The study found that level of knowledge on KOSPEN is associated with employment status (p=0.02) and awareness level (p<0.001) among the community health volunteers. The level of implementation is associated with age (p=0.025), education level (p=0.007) and employment status (p=0.017) of the community health volunteers. Employment status (aOR=2.133, 95% CI=1.056-4.306, p=0.035) and awareness level (aOR=6.119, 95% CI=2.701-13.867 p<0.001) were predictors of level of knowledge on KOSPEN. Level of implementation of KOSPEN by the community health volunteers could be predicted by education level (aOR=4.085, 95% CI=1.299-12.851 p=0.016). Conclusion: Generally the KOSPEN volunteers had good knowledge on KOSPEN and implementation of KOSPEN program. However, there are still misconceptions among the KOSPEN volunteers regarding their functions and role. Therefore it is important to empower the volunteers with awareness on their roles, functions and good knowledge.